Kedudukan International Criminal Police Organization (ICPO-Interpol) dalam Perjanjian Ekstradisi antara Indonesia dan Australia - Christien Pristi Gresilo Putri Amanda; Veriena Josepha Batseba Rehatta; Richard Marsilio Waas (Faculty of Law, Universitas Pattimura, 2021)
Introductioan: There are advances in science and technology, especially in transportation and communication technology that make it easier for people to move from one country to another. The movement of people from one country to another has been taken advantage of by criminals in an attempt to escape punishment, such as the case of Adrian Kiki Ariawan who fled to Australia. Therefore, international cooperation is needed through the involvement of Extradition and ICPO-Interpol.Purposes of the Research: To analyze and review the implementation of the extradition treaty between Indonesia and Australia. And to analyze and study the position of ICPO-Interpol in the extradition treaty between Indonesia and Australia.Results of the Research: This research uses normative juridical research with the legal materials used in the research are primary, secondary and tertiary data using library study techniques in the form of Law No.1 of 1979 on Extradition, scientific papers and literature.